Communication Strategy for Spald-T Development via YouTube in Haurwangi Village, Cianjur - Yessi Sri Utami; Pupu Jamilah; Aria Bagus Cahyana (Communicatus: Jurnal Ilmu komunikasi, 2023)
Domestic wastewater is a complex problem, especially in rural areas with low-income (MBR) people. People throw away domestic waste, including dumping large amounts directly into rivers, which results in river pollution. This research aims to identify how the development of communication strategies through YouTube media and interpersonal media can be helpful for local communities in solving health problems. Communication strategy for developing a Centralized Domestic Wastewater Treatment System (SPALD-T) in Haurwangi Village, Kec. Haurwangi District. Cianjur uses YouTube media and interpersonal media. This research uses a case study method with a qualitative approach. Data collection techniques were carried out using interviews, observation and documentation. The research results show that YouTube media can give the public an understanding of the importance of pursuing wastewater management with salad-t because it is considered relevant. The community under KSM coordination feels the benefits and convenience of managing domestic waste and understands that the Spald-t technology is easy to use and can be tested and implemented within six months. The existence of videos on KSM YouTube shows participation and feedback from the community regarding the SPALD-T development program, which has been well received, and the benefits can be felt.